Environmental Communication And Ecolinguistic Studies In Plastic Waste Management Discourse On Social Media - Nasoetion, Panisean; Samhati, Siti (KOMUNIKA, 2024)
This research examines environmental communication patterns and ecolinguistic aspects in plastic waste management discourse conducted by the @waste4change social media account. The research focuses on communication strategies, language use, and their impact on environmental awareness through a qualitative approach with critical discourse analysis. Data were collected through social media content documentation, in-depth interviews, and digital observation during the period of January-June 2024. The results show that @waste4change uses an integrative communication strategy with emphasis on educational and practical aspects. Ecolinguistic studies reveal consistent use of environmental lexicons, effective ecological metaphors, and positive framing in message delivery. The developed communication patterns have successfully built community engagement and encouraged behavioral changes in plastic waste management. These findings provide theoretical implications for developing digital-based environmental communication models and understanding the role of language in environmental campaigns. This research recommends the importance of integrating linguistic aspects into environmental communication strategies in the digital era.